Electrode plate for non-aqueous electrolyte storage element, non-aqueous electrolyte storage element, and method for manufacturing electrode plate for non-aqueous electrolyte storage element
Patent Information
- Application Number
- JP2020219388
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-28
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-28
AI Technical Summary
【0010】 本発明によれば、充放電を繰り返しても出力保持率の低下が抑制された非水電解質蓄電素子の極板、非水電解質蓄電素子及び非水電解質蓄電素子の極板の製造方法を提供することができる。
Smart Images

Figure 0007631804000002 
Figure 0007631804000003 
Figure 0007631804000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode plate for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for manufacturing an electrode plate for a nonaqueous electrolyte storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.
[0003] The electrode plate of the nonaqueous electrolyte storage element generally has a structure in which a mixture layer containing an active material is formed on the surface of a conductive substrate such as a metal foil. This mixture layer is formed by applying a slurry mixture containing an active material and drying it. For example, Patent Document 1 proposes a slurry composition for a lithium ion secondary battery negative electrode, which contains a carbon material (amorphous carbon material) having an interlayer distance of 0.340 to 0.370 nm as a negative electrode active material, polymer particles as a binder, and a thickener having a specific degree of polymerization, and a lithium ion secondary battery negative electrode obtained from the composition. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2011 / 096463 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] On the other hand, in a nonaqueous electrolyte storage element, repeated charging and discharging can cause a bias between the concentration of the charge transfer medium (e.g., Li ions) in the nonaqueous electrolyte contained at one end and the other end of the electrode body and the concentration of the charge transfer medium in the nonaqueous electrolyte contained in the center of the electrode body, resulting in an increase in the internal resistance of the nonaqueous electrolyte storage element. If the internal resistance of the nonaqueous electrolyte storage element increases in this way, there is a risk of a significant decrease in the output of the nonaqueous electrolyte storage element.
[0006] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide an electrode plate for a nonaqueous electrolyte storage element in which a decrease in output retention rate is suppressed even when charging and discharging are repeated, a nonaqueous electrolyte storage element, and a method for manufacturing an electrode plate for a nonaqueous electrolyte storage element. [Means for solving the problem]
[0007] One aspect of the present invention made to solve the above-mentioned problems is an electrode plate for a nonaqueous electrolyte storage element, comprising a substrate, and a mixture layer containing an active material and a conductive agent including a carbonaceous material, the mixture layer being laminated on the substrate, wherein when the mixture layer is divided in the thickness direction into a surface side region and a substrate side region, the average concentration ratio of carbon elements in the surface side region to the substrate side region is greater than 1, and when the mixture layer is further divided into a first end region at one end in the width direction, a second end region at the other end in the width direction, and a central region disposed between the first end region and the second end region, the average concentration ratio (E2 / E1) of carbon elements in the surface side region (E2) of the first end region to the substrate side region (E1) in the first end region is greater than 1.20 times the average concentration ratio (C2 / C1) of carbon elements in the surface side region (C2) of the central region to the substrate side region (C1) of the central region.
[0008] Another embodiment of the present invention is a nonaqueous electrolyte electricity storage element including the electrode plate.
[0009] Another aspect of the present invention is a method for manufacturing an electrode plate for a nonaqueous electrolyte storage element comprising a substrate and a composite layer containing a conductive agent and an active material including a carbonaceous material and laminated on the substrate, the method comprising: applying a composite paste containing the conductive agent and the active material to the substrate; and drying the coating layer of the composite paste, wherein a drying temperature of an end region in a width direction of the coating layer is higher than a drying temperature of a central region in the width direction of the coating layer. Effect of the Invention
[0010] According to the present invention, it is possible to provide an electrode plate for a nonaqueous electrolyte storage element in which a decrease in output retention rate is suppressed even when charging and discharging are repeated, a nonaqueous electrolyte storage element, and a method for manufacturing an electrode plate for a nonaqueous electrolyte storage element. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic exploded perspective view showing an electrode assembly and a container of a nonaqueous electrolyte storage element according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing an electrode plate of a nonaqueous electrolyte storage element according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] An electrode plate for a nonaqueous electrolyte storage element (hereinafter also simply referred to as an "energy storage element") according to one embodiment of the present invention comprises a substrate, and a mixture layer containing an active material and a conductive agent including a carbonaceous material, the mixture layer being laminated on the substrate; when the mixture layer is divided in the thickness direction into a surface side region and a substrate side region, the average concentration ratio of carbon elements in the surface side region to the substrate side region is greater than 1; and when the mixture layer is further divided into a first end region at one end in the width direction, a second end region at the other end in the width direction, and a central region disposed between the first end region and the second end region, the average concentration ratio (E2 / E1) of carbon elements in the surface side region (E2) of the first end region to the substrate side region (E1) of the first end region is greater than 1.20 times the average concentration ratio (C2 / C1) of carbon elements in the surface side region (C2) of the central region to the substrate side region (C1) of the central region.
[0013] A nonaqueous electrolyte storage element having such an electrode plate is prevented from decreasing in output retention even when repeatedly charged and discharged. Although the reason for this is not clear, the following reason is presumed. For example, the mixture layer of the electrode body receives a larger amount of non-aqueous electrolyte in the widthwise end regions than in the widthwise central region, and the non-aqueous electrolyte is more likely to be depleted in the widthwise central region. In addition, the non-aqueous electrolyte is less likely to permeate the substrate side region than the surface side region, and in particular, the substrate side region in the widthwise central region of the mixture layer is the least likely to be permeated by the non-aqueous electrolyte. Therefore, the average concentration ratio of carbon element in the surface side region to the substrate side region is greater than 1, and the surface side region (E2) to the substrate side region (E1) is Charcoal The average concentration ratio (E2 / E1) of the element in the surface side region (C2) to the substrate side region (C1) is Charcoal By distributing the conductive agent in the widthwise end regions more than in the widthwise central region so that the ratio of the average concentration ratio of elemental elements (C2 / C1) is greater than 1.20 times, the movement of the charge transfer medium (e.g., Li ions) of the non-aqueous electrolyte from the widthwise end regions to the widthwise central region is promoted, and the diffusibility of the charge transfer medium is improved. More specifically, it is presumed that the diffusibility of the charge transfer medium to the substrate side region (C1) of the central region is improved via the substrate side region (E1) of the first end region, where the concentration of carbon elements derived from the carbonaceous material as the conductive agent is relatively low. As a result, the concentration bias of the charge transfer medium of the non-aqueous electrolyte can be suppressed, and the decrease in the output retention rate during repeated charging and discharging of the non-aqueous electrolyte storage element having the electrode plate can be suppressed. The present invention can be more effective in a wound electrode body.
[0014] Here, the end region refers to a region in which the volume ratio of the mixture layer to the total volume is 20% or less from the first end and second end, which are both ends when the mixture layer is divided in the width direction, toward the inside. The central region refers to a region other than the first end region and the second end region on both ends. In addition, the surface side region refers to a region in which the volume ratio of the mixture layer to the total volume is 50% or less from the surface side toward the substrate when the mixture layer is divided in the thickness direction, and the substrate side region refers to a region in which the volume ratio of the mixture layer to the total volume is 50% or less from the upper surface side of the substrate toward the surface.
[0015] The median diameter of the particles of the active material is preferably 7 μm or less. When the median diameter of the particles of the active material is 7 μm or less, the diffusibility of the nonaqueous electrolyte in the mixture layer is improved, so that the decrease in the output retention rate during repeated charging and discharging of a nonaqueous electrolyte storage element having the electrode plate can be further suppressed.
[0016] It is preferable that the average concentration ratio (E4 / E3) of carbon element in the surface side region (E4) of the second end region to the substrate side region (E3) of the second end region is greater than 1.20 times the average concentration ratio (C2 / C1). By making the average concentration ratio (E4 / E3) of the surface side region (E4) to the substrate side region (E3) in the second end region as well as the first end region greater than 1.20, the diffusibility of the charge transfer medium from both ends in the width direction to the central region is improved, and the decrease in the output retention rate during repeated charging and discharging of a nonaqueous electrolyte storage element having the electrode plate can be further suppressed.
[0017] A nonaqueous electrolyte storage element according to one embodiment of the present invention includes the above-described electrode plates, which makes it possible to suppress a decrease in output retention rate during repeated charging and discharging.
[0018] A method for manufacturing an electrode plate for a non-aqueous electrolyte storage element according to one embodiment of the present invention is a method for manufacturing an electrode plate for a non-aqueous electrolyte storage element comprising a substrate and a composite layer containing a conductive agent and an active material including a carbonaceous material and laminated on the substrate, the method comprising the steps of: applying a composite paste containing the conductive agent and the active material to the substrate; and drying the coating layer of the composite paste, wherein a drying temperature of an end region in a width direction of the coating layer is higher than a drying temperature of a central region in a width direction of the coating layer.
[0019] According to the method for manufacturing an electrode plate for the nonaqueous electrolyte storage element, the drying temperature of the end regions in the width direction of the coating layer is higher than the drying temperature of the central region in the width direction of the coating layer, and therefore the average concentration ratio (E2 / E1) of the carbon elements in the end regions becomes larger, and the electrode plate can be manufactured easily.
[0020] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, a method for manufacturing an electrode plate of a nonaqueous electrolyte storage element, ... and an electrode plate of a nonaqueous electrolyte storage element according to one embodiment of the present invention will be described in detail with reference to the drawings.
[0021] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode, the negative electrode, or a combination thereof of the nonaqueous electrolyte storage element is composed of an electrode plate according to one embodiment of the present invention. A nonaqueous electrolyte secondary battery, which is an example of the nonaqueous electrolyte storage element, will be described below. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in an exterior body (case), and the exterior body (case) is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode.
[0022] FIG. 1 is a schematic exploded perspective view showing an electrode body and a container of a nonaqueous electrolyte storage element according to one embodiment of the present invention. The nonaqueous electrolyte storage element 1 includes an electrode body 2, a positive electrode current collector 4' and a negative electrode current collector 5' connected to both ends of the electrode body 2, and an exterior body 3 that houses them. In the nonaqueous electrolyte storage element 1, the electrode body 2 is housed in the exterior body 3, and a nonaqueous electrolyte is disposed in the exterior body 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material and a negative electrode having a negative electrode active material in a flat shape with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via the positive electrode current collector 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via the negative electrode current collector 5'.
[0023] The exterior body 3 is a rectangular parallelepiped housing that houses the electrode assembly 2, the positive electrode current collector 4', and the negative electrode current collector 5', and has one surface (top surface) perpendicular to the X direction, which is the longitudinal direction of the housed positive electrode current collector 4', open. Specifically, the exterior body 3 has a bottom surface, a pair of long side surfaces facing each other in the Y direction, which is the thickness direction of the electrode assembly 2, and a pair of short side surfaces facing each other in the Z direction, which is the width direction of the electrode assembly 2. The top surface is closed by a lid 6. The exterior body 3 and the lid 6 are made of a metal plate. For example, aluminum can be used as the material of this metal plate.
[0024] The lid 6 is provided with a positive electrode terminal 4 and a negative electrode terminal 5 that are electrically connected to the outside. The positive electrode terminal 4 is connected to a positive electrode current collector 4', and the negative electrode terminal 5 is connected to a negative electrode current collector 5'. A non-aqueous electrolyte is injected into the exterior body 3 through an injection hole (not shown) provided in the lid 6.
[0025] The electrode body 2 has a positive electrode, a negative electrode, and a separator that insulates them, and the positive electrodes and negative electrodes are alternately stacked with the separator interposed therebetween. The electrode body 2 is a wound type electrode body in which a sheet body including a positive electrode, a negative electrode, and a separator is wound into a flat shape. That is, the electrode body 2 has an elliptical shape having a minor axis and a major axis when viewed in the direction of the winding axis.
[0026] <Pole plate> The electrode plate includes a substrate and a composite layer containing a conductive agent including a carbonaceous material and an active material and laminated on the substrate. The composite layer may be laminated on the substrate directly or via an intermediate layer. FIG. 2 is a schematic cross-sectional view showing an electrode plate of a nonaqueous electrolyte storage element according to one embodiment of the present invention. As shown in FIG. 2, the electrode plate 10 includes a substrate 12 and a composite layer 13 laminated on the substrate 12. As in FIG. 1, in FIG. 2, the Y direction is the thickness direction of the electrode body 2 (composite layer 13), and the Z direction is the width direction of the electrode body 2 (composite layer 13).
[0027] [Base material] The substrate is electrically conductive.
[0028] The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum and aluminum alloys are preferred from the viewpoint of the balance between potential resistance, high conductivity, and cost. The positive electrode substrate may be formed in the form of foil, vapor deposition film, or the like, and foil is preferred from the viewpoint of cost. That is, aluminum foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085, A3003, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0029] The negative electrode substrate can be formed in the same manner as the positive electrode substrate, but the material is a metal such as copper, nickel, stainless steel, nickel-plated steel, or an alloy thereof, and copper or a copper alloy is preferred. That is, the negative electrode substrate is preferably a copper foil. Examples of the copper foil include rolled copper foil and electrolytic copper foil.
[0030] [Mixture layer] The mixture layer contains a conductive agent containing a carbonaceous material and an active material. The mixture layer is formed from a so-called mixture containing an active material. The mixture forming the mixture layer contains optional components such as a binder (binding agent), a thickener, and a filler as necessary, in addition to the conductive agent containing a carbonaceous material and the active material.
[0031] (Conductive agent) The conductive agent is not particularly limited as long as it contains a carbonaceous material. Examples of such conductive agents include natural or artificial graphite, furnace black, acetylene black, and carbon black such as Ketjen black. The conductive agent may be in the form of a powder or fiber. The upper limit of the particle size of the conductive agent is preferably 100 nm, more preferably 80 nm. In general, the conductive agent has a relatively small particle size compared to the active material described below, and therefore is easily inserted between the active materials. Therefore, in a region where the content of the conductive agent in the mixture layer is relatively high (for example, the surface region described below), the voids in the mixture layer are smaller than in a region where the content of the conductive agent is relatively low (for example, the substrate side region described below). Therefore, in a region where the content of the conductive agent is relatively low, it is presumed that the diffusibility of the charge transfer medium of the nonaqueous electrolyte contained in the voids is relatively better than in a region where the content of the conductive agent is relatively high. When the upper limit of the particle size of the conductive agent containing the carbonaceous material is the above value, this tendency is particularly noticeable. The lower limit of the particle size of the conductive agent is preferably 10 nm, and more preferably 20 nm. The particle size of the conductive agent is the particle size measured by a scanning electron microscope (SEM). Specifically, the particle size of the conductive agent is measured by the following method. The electric storage element discharged to the end of discharge is disassembled in an environment with a dew point of -20°C or less. The electrolyte adhering to the electrode plate is washed away using dimethyl carbonate (DMC), and then the solvent is dried and removed from the electrode plate. The cross section of the electrode plate that has been cross-sectionally processed by a cross-section polisher is observed by a scanning electron microscope (SEM). The average value of the maximum diameter of at least 20 randomly selected conductive agents is calculated to be the particle size of the conductive agent.
[0032] 2, the mixture layer 13 can be divided into first end regions E1 and E2 at one end in the width direction, second end regions E3 and E4 at the other end in the width direction, and central regions C1 and C2 disposed between the first and second end regions, as regions having different average concentration ratios of carbon elements in the mixture layer 13. More specifically, the mixture layer 13 can be divided into six regions: a substrate side region E1 in the first end region, a surface side region E2 in the first end region, a substrate side region E3 in the second end region, a surface side region E4 in the second end region, a substrate side region C1 in the central region, and a surface side region C2 in the central region.
[0033] When the mixture layer is divided into a surface side region and a substrate side region in the thickness direction, the lower limit of the average concentration ratio of carbon elements in the surface side region (E2, C2, E4) to the substrate side region (E1, C1, E3) is more than 1, preferably 1.10, more preferably 1.20 or more, and even more preferably 1.30 or more. When the lower limit of the average concentration ratio of carbon elements in the surface side region to the substrate side region is the above value, it is possible to suppress a decrease in output retention rate during repeated charging and discharging. In addition, the upper limit of the average concentration ratio of carbon elements in the surface side region to the substrate side region is preferably 1.50 from the viewpoint of suppressing a decrease in current collecting ability.
[0034] The lower limit of the ratio of the average concentration ratio (E2 / E1) of the carbon element in the surface side region (E2) to the substrate side region (E1) to the average concentration ratio (C2 / C1) of the carbon element in the surface side region (C2) to the substrate side region (C1) is more than 1.20, preferably 1.30, and more preferably 1.40. By setting the lower limit of the ratio of the average concentration ratio (E2 / E1) to the average concentration ratio (C2 / C1) to the above value, the output retention rate in the charge / discharge cycle can be increased. In addition, the upper limit of the ratio of the average concentration ratio (E2 / E1) to the average concentration ratio (C2 / C1) is preferably 2.00 from the viewpoint of suppressing a decrease in current collecting ability.
[0035] The lower limit of the ratio of the average concentration ratio (E4 / E3) of the surface side region (E4) to the substrate side region (E3) to the average concentration ratio (C2 / C1) is more than 1.20, preferably 1.30, and more preferably 1.40. Furthermore, by setting the lower limit of the ratio of the average concentration ratio (E4 / E3) to the average concentration ratio (C2 / C1) to the above value, the output retention rate in the charge / discharge cycle can be increased. Moreover, the upper limit of the ratio of the average concentration ratio (E4 / E3) to the average concentration ratio (C2 / C1) is preferably 2.00 from the viewpoint of suppressing a decrease in current collecting ability. The average concentration of carbon element in each region of the mixture layer 13 is determined by line analysis measurement of the concentration of carbon element in any cross section parallel to the width direction of the electrode plate using an electron probe microanalyzer (EPMA). For the end region, the concentration of carbon element is measured over the entire thickness direction of the electrode plate at a position in the width direction where the ratio of the volume of the mixture layer to the total volume of the mixture layer is 10% from the first end and the second end, which are both ends when the mixture layer is divided in the width direction, toward the inside. For the central region, the concentration of carbon element is measured over the entire thickness direction of the electrode plate at a position in the width direction where the ratio of the volume of the mixture layer to the total volume of the mixture layer is 50% from the first end and the second end, which are both ends when the mixture layer is divided in the width direction, toward the inside. For each region, the average value in the thickness direction is taken as the carbon element concentration of the region. The average concentration of carbon element in the substrate side region is taken as the average value of the carbon element concentrations in the E1, C1 and E3 regions calculated as described above, and the average concentration of carbon element in the surface side region is taken as the average value of the carbon element concentrations in the E2, C2 and E4 regions calculated as described above.
[0036] (active material) The positive electrode active material is, for example, Li x MO y (M represents at least one transition metal) 2 Li with type crystal structure x Chief of Staff 2、 Li x NiO 2、 Li x MnO 3、 Li x Ni α Co (1-α) O 2、 Li x Ni α Mn β Co (1-α-β) O 2 Li with spinel crystal structure x Mn 2 O 4、 Li x Ni α Mn (2-α) O 4 etc.), Li w Me x (XOy ) z (Me represents at least one transition metal, and X represents, for example, P, Si, B, V, etc.) 4、 LiMnPO 4、 LiNiPO 4、 LiCoPO 4、 Li 3 V 2 (PO 4 ) 3、 Li 2 MnSiO 4、 Li 2 CoPO 4 F, etc. The elements or polyanions in these compounds may be partially substituted with other elements or anion species. In the positive electrode mixture layer, one of these compounds may be used alone, or two or more of them may be used in combination.
[0037] The negative electrode active material is a material capable of absorbing and releasing lithium ions. Specific examples of the negative electrode active material include metals or semimetals such as Si and Sn, metal oxides or semimetal oxides such as Si oxide and Sn oxide, polyphosphate compounds, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon).
[0038] Furthermore, the negative electrode mixture may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W.
[0039] The upper limit of the median diameter of the active material particles is preferably 4 μm, more preferably 7 μm. By setting the upper limit of the median diameter of the active material particles to the above value, the diffusibility of the non-aqueous electrolyte in the mixture layer is further improved, so that the decrease in the output retention rate during repeated charging and discharging can be suppressed. In addition, the lower limit of the median diameter of the active material particles is preferably 2 μm. By setting the median diameter of the active material particles to 2 μm or more, the flow of the mixture paste described below occurs appropriately.
[0040] The above-mentioned "median diameter" means the value (D50) at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%. Specifically, it can be a measured value by the following method. Measurement is performed using a laser diffraction particle size distribution measuring device (Shimadzu Corporation's "SALD-2200") as the measuring device and Wing SALD-2200 as the measurement control software. A scattering measurement mode is adopted, and a laser beam is irradiated onto a wet cell in which a dispersion liquid in which the measurement sample is dispersed in a dispersion solvent is circulated, and a scattered light distribution is obtained from the measurement sample. The scattered light distribution is then approximated by a log-normal distribution, and the particle diameter at which the cumulative degree is 50% is taken as the median diameter (D50). It has been confirmed that the median diameter based on the above measurement is almost the same as the median diameter measured by extracting 100 particles from an SEM image, avoiding extremely large and extremely small particles. The diameter of each particle measured from the SEM image is the Feret diameter, and the volume of each particle is calculated assuming that it is a sphere with the Feret diameter as its diameter.
[0041] (Other optional ingredients) Examples of the binder (binding agent) include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0042] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.
[0043] The filler is not particularly limited, and examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, and glass.
[0044] The lower limit of the porosity of the mixture layer is preferably 25%, more preferably 30%. The upper limit of the porosity is preferably 50%, more preferably 45%. By having the porosity in the above range, the capacity retention rate of a nonaqueous electrolyte storage element using the negative electrode active material on the substrate side of the mixture layer can be further increased.
[0045] The "porosity" of the mixture layer refers to a value calculated from the true density of the mixture calculated from the true density of each component constituting the mixture layer and the packing density according to the following formula. Porosity (%)=100-(filling density / true density)×100 Here, the "packing density" refers to the mass of the mixture divided by the apparent volume of the mixture. The apparent volume refers to the volume including voids, and when the mixture is layered, it can be calculated as the product of the thickness and area of the mixture.
[0046] [Middle layer] The intermediate layer is a coating layer on the surface of the substrate, and contains a conductive agent such as carbonaceous material particles to reduce the contact resistance between the substrate and the composite layer. The configuration of the intermediate layer is not particularly limited, and it can be formed, for example, from a composition containing a binder and a conductive agent. The term "conductive" means that the intermediate layer has a volume resistivity of 10 or more as measured in accordance with JIS-H-0505 (1975). 7 "Non-conductive" means that the volume resistivity is 10 7 This means that the resistance is greater than Ω·cm.
[0047] <Method for manufacturing electrode plates of non-aqueous electrolyte storage element> A method for manufacturing an electrode plate of a nonaqueous electrolyte storage element according to one embodiment of the present invention includes coating the base material with a mixture paste containing the conductive agent and the active material, and drying the coating layer of the mixture paste.
[0048] The mixture paste generally uses an organic solvent as a dispersion medium. Examples of the organic solvent include polar solvents such as N-methyl-2-pyrrolidone (NMP), acetone, and ethanol, and non-polar solvents such as xylene, toluene, and cyclohexane. Polar solvents are preferred, and NMP is more preferred. In addition to these, the mixture paste can contain each optional component that may be contained in the above-mentioned positive electrode mixture.
[0049] As a means for kneading the mixture paste, for example, a method using Filmix (registered trademark) manufactured by Primix Corporation can be mentioned.
[0050] The method for applying the mixture paste is not particularly limited, and can be any known method such as roller coating, screen coating, or spin coating.
[0051] Examples of drying means for the coating layer include hot air drying and IR heaters, and examples of drying methods include continuous and batch drying. The drying temperature is preferably 100° C. or higher and 150° C. or lower. The drying speed in the continuous method is preferably 1 m / min. or higher and 20 m / min. or lower.
[0052] In addition, in the method for manufacturing an electrode plate for a nonaqueous electrolyte storage element according to one embodiment of the present invention, the drying temperature of the end region in the width direction of the coating layer is higher than the drying temperature of the central region in the width direction of the coating layer. In the process of drying the coating layer, the mixture paste flows with the evaporation of the dispersion medium. When the mixture paste flows, the components of the mixture paste having a smaller particle size tend to move toward the surface side of the coating layer (the side opposite to the substrate) more than the components having a larger particle size. This tendency becomes stronger when the drying temperature is high. As described above, the conductive agent containing a carbonaceous material generally has a smaller particle size than the active material. Therefore, the drying temperature of the end region in the width direction of the coating layer is higher than the drying temperature of the central region in the width direction of the coating layer, so that the average concentration ratio (E2 / E1) of the carbon element in the end region can be increased. An example of a drying means for the end region is an IR heater. In addition, the drying temperature of the end region is preferably 150° C. or higher and 250° C. or lower.
[0053] [Separator] As the separator, for example, a woven fabric, a nonwoven fabric, a porous resin film, etc. are used. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of nonaqueous electrolyte retention. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferable from the viewpoint of strength, and a polyimide or aramid is preferable from the viewpoint of oxidation decomposition resistance. These resins may also be combined.
[0054] An inorganic layer may be disposed between the separator and the electrode plate (usually a positive electrode). This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one side of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components.
[0055] [Non-aqueous electrolyte] The nonaqueous electrolyte may be any known nonaqueous electrolyte that is commonly used in general nonaqueous electrolyte storage elements. The nonaqueous electrolyte contains a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0056] The non-aqueous solvent may be a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, nitriles, etc. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate.
[0057] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate, with EC being preferred.
[0058] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, and the like. Among these, EMC is preferable.
[0059] Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts, and the like, with lithium salts being preferred. The lithium salt is LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiPF 2 (C 2 O 4 ) 2 , LiClO4 , LiN(SO 2 F) 2 Inorganic lithium salts such as LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 ) 3 and the like.
[0060] The non-aqueous electrolyte may contain other additives. Furthermore, an ionic liquid or the like may be used as the non-aqueous electrolyte.
[0061] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The nonaqueous electrolyte storage element can be manufactured by combining known manufacturing methods, but is preferably manufactured by the following method. The manufacturing method of the nonaqueous electrolyte storage element according to one embodiment of the present invention includes the manufacturing method of the electrode plate of the nonaqueous electrolyte storage element described above. The manufacturing method of the nonaqueous electrolyte storage element according to one embodiment of the present invention includes, for example, a step of manufacturing a positive electrode by the manufacturing method of the electrode plate of the nonaqueous electrolyte storage element. In addition to the step of manufacturing the positive electrode, the manufacturing method of the nonaqueous electrolyte storage element may include the following steps. That is, the manufacturing method of the nonaqueous electrolyte storage element can include, for example, a step of manufacturing a negative electrode, a step of preparing a nonaqueous electrolyte, a step of forming an electrode body in which the positive electrode and the negative electrode are alternately stacked by stacking or rolling them with a separator interposed therebetween, a step of housing the positive electrode and the negative electrode (electrode body) in an exterior body (case), and a step of injecting the nonaqueous electrolyte into the exterior body. The injection can be performed by a known method. After the injection, the injection port is sealed to obtain a nonaqueous electrolyte storage element.
[0062] [Other embodiments] The nonaqueous electrolyte electricity storage element of the present invention is not limited to the above-described embodiment.
[0063] In the above embodiment, the nonaqueous electrolyte storage element is mainly a secondary battery, but other nonaqueous electrolyte storage elements may be used. Examples of other nonaqueous electrolyte storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc.
[0064] The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte electricity storage elements. A single or a plurality of the nonaqueous electrolyte electricity storage elements (cells) of the present invention can be used to form a battery pack, and this battery pack can be used to form an electricity storage device. The electricity storage device can be used as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0066] [Example 1] (Preparation of positive electrode) As the positive electrode active material, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 As the dispersion medium, N-methyl-2-pyrrolidone (NMP) was used. As the conductive agent, acetylene black was used. As the binder, polyvinylidene fluoride (PVDF) was used. The positive electrode active material, the conductive agent, and the binder were mixed and kneaded in a mass ratio of 90:5:5 in terms of solid content to obtain a positive electrode mixture paste. This positive electrode mixture paste was applied to one side of an aluminum foil, which was a positive electrode substrate, to form a coating layer of the positive electrode mixture paste. A continuous drying oven was used as a drying means for the central region in the width direction of the coating layer, with the drying temperature set to 120°C in the first drying oven and 130°C in the second drying oven, and the drying speed set to 2 m / min. An IR heater was used as a drying means for the end regions in the width direction of the coating layer, with the drying temperature set to 180°C. In this manner, the coating layer was dried to form a positive electrode mixture on the positive electrode substrate. The coating amount of the positive electrode mixture paste was 10 mg / cm in solid content. 2 In this way, a positive electrode was obtained. The average concentration ratio of carbon element in the surface side region to the substrate side region of the positive electrode mixture layer was 1.36, the average concentration ratio (C2 / C1) in the central region was 1.17, the average concentration ratio (E2 / E1) in the first end portion was 1.65, and the magnification of the average concentration ratio (E2 / E1) to the average concentration ratio (C2 / C1) was 1.41. In addition, the median diameter of the particles of the positive electrode active material was 4.3 μm.
[0067] (Preparation of negative electrode) The negative electrode active material used was non-graphitizable carbon.
[0068] (Preparation of non-aqueous electrolyte) LiPF was added to a mixed solvent of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:40:30.6 to 1.0 mol / dm 3 A non-aqueous electrolyte was prepared by dissolving the aqueous solution in the above-mentioned solution at a concentration of 1:1.
[0069] (Preparation of non-aqueous electrolyte storage element) A polyethylene separator was used as the separator. The positive electrode and the negative electrode were laminated with the separator interposed therebetween to produce an electrode body. The electrode body was housed in an exterior body (case) made of a metal resin composite film, and the nonaqueous electrolyte was injected inside, and then the case was sealed by heat welding to obtain a nonaqueous electrolyte storage element.
[0070] [Example 2 and Comparative Examples 1 to 2] Non-aqueous electrolyte storage elements of Example 2 and Comparative Example 1 to Comparative Example 2 were obtained in the same manner as in Example 1, except that the drying conditions for the widthwise end regions of the coating layer and the median diameter of the positive electrode active material were as shown in Table 1.
[0071] [evaluation] (Charge-discharge cycle test under high temperature: output retention rate) Next, the following 55°C cycle test was performed on each of the nonaqueous electrolyte storage elements of each Example and Comparative Example. That is, at a temperature of 55°C, charging and discharging were repeated for 1000 hours at a current value of 5C with a SOC (State of Charge) in the range of 15% to 85%. Before and after that, the output value at 25°C was calculated, and the output retention rate (%) was calculated. The output value and the output retention rate were calculated as follows. A nonaqueous electrolyte storage element with an SOC of 50% was discharged at current values of 1C, 2C, 3C, 4C, and 5C, and an IV plot was drawn using the voltage at 1 second after the start of discharge. Then, the current value at the lower limit voltage of 2.5V was obtained by extrapolation, and the output value was calculated by multiplying the current value and the voltage. As the output retention rate, the ratio of the output value after the charge-discharge cycle test to the output value before the charge-discharge cycle test was obtained. The calculation results of the output retention rate are shown in Table 1. In Table 1, the ratio of the output retention rate of Example 1 to the output retention rate of Comparative Example 1 and the ratio of the output retention rate of Example 2 to the output retention rate of Comparative Example 2 are each shown as a percentage.
[0072] [Table 1]
[0073] As shown in Table 1, Example 1, in which the average concentration ratio of carbon element in the surface side region to the substrate side region is greater than 1 and the ratio of the average concentration ratio (E2 / E1) in the first end region to the average concentration ratio (C2 / C1) in the central region is greater than 1.20, had a better output retention at 25°C even after repeated charging and discharging than Comparative Example 1, in which the ratio was 1.20 or less. Similarly, Example 2, in which the ratio of the average concentration ratio (E2 / E1) to the average concentration ratio (C2 / C1) is greater than 1.20, had a better output retention than Comparative Example 2, in which the ratio was 1.20 or less. Furthermore, the results of Examples 1 and 2 show that when the median diameter of the active material particles is 7 μm or less, the decrease in output retention rate during repeated charging and discharging of the nonaqueous electrolyte storage element can be further suppressed. [Industrial Applicability]
[0074] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0075] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 Exterior body 4 Positive terminal 4' Positive electrode current collector 5 Negative terminal 5' Negative electrode current collector 6 Lid 10 plate 12 Base material 13 Mixture layer E1: Substrate side region of first end region E2 Surface side region of the first end region C1: Central region on the substrate side C2 Surface side area of the central area E3 Substrate side region of second end region E4 Surface side region of the second end region
Claims
1. A substrate; a composite layer containing a conductive agent including a carbonaceous material and an active material and laminated on the substrate; Equipped with When the mixture layer is divided in a thickness direction into a surface side region and a substrate side region, the average concentration ratio of carbon element in the surface side region to the substrate side region is more than 1 and 1.50 or less, when the mixture layer is further divided into a first end region on one end side in the width direction, a second end region on the other end side in the width direction, and a central region disposed between the first end region and the second end region, an average carbon element concentration ratio (E2 / E1) of the surface side region (E2) of the first end region to the substrate side region (E1) of the first end region is more than 1.20 times and not more than 2.00 times an average carbon element concentration ratio (C2 / C1) of the surface side region (C2) of the central region to the substrate side region (C1) of the central region, The active material of the electrode plate of the nonaqueous electrolyte storage element is at least one selected from the group consisting of a composite oxide represented by LixMOy (M represents at least one transition metal, and elements in the active material may be partially substituted with other elements), a polyanion compound represented by LiwMex(XOy)z (Me represents at least one transition metal, X represents P, Si, B or V, and elements in the active material may be partially substituted with other elements), a metal, a semi-metal, a metal oxide, a semi-metal oxide, and a polyphosphate compound.
2. 2. The electrode plate of claim 1, wherein the median particle size of said active material is 7 [mu]m or less.
3. An electrode plate for a nonaqueous electrolyte storage element according to claim 1 or claim 2, wherein the average concentration ratio (E4 / E3) of carbon element in the surface side region (E4) of the second end region to the substrate side region (E3) of the second end region is more than 1.20 times and not more than 2.00 times the average concentration ratio (C2 / C1).
4. A non-aqueous electrolyte electricity storage element comprising the electrode plate according to claim 1, 2 or 3.
5. A method for manufacturing an electrode plate according to claim 1, claim 2 or claim 3, comprising the steps of: A method for producing an electrode plate for a nonaqueous electrolyte storage element, comprising: a substrate; and a mixture layer that contains a conductive agent including a carbonaceous material and an active material and is laminated on the substrate, the method comprising the steps of: Applying a mixture paste containing the conductive agent and the active material to the substrate; drying the coating layer of the mixture paste; Equipped with A method for producing an electrode plate for a nonaqueous electrolyte storage element, wherein the drying temperature of the end regions in the width direction of the coating layer is higher than the drying temperature of the central region in the width direction of the coating layer.
Citation Information
Patent Citations
Nickel electrode for alkaline storage battery, and its manufacture
JP1996203514A
Nonaqueous electrolyte secondary battery and manufacturing method of electrode for nonaqueous electrolyte secondary battery
JP2008311164A
Electrode plate for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2012028006A
Positive electrode for lithium secondary battery and lithium secondary battery including the same
JP2020501328A
Slurry composition for negative electrode of lithium ion secondary battery, negative electrode of lithium ion secondary battery, and lithium ion secondary battery
WO2011096463A1